Cancer anti-angiogenesis vaccines: Is the tumor vasculature antigenically unique?. Issue 1 (December 2015) - Wagner, Samuel; Ichim, Thomas; Ma, Hong; Szymanski, Julia; Perez, Jesus; Lopez, Javier; Bogin, Vladimir; Patel, Amit; Marincola, Francisco; Kesari, Santosh
Abstract Angiogenesis is essential for the growth and metastasis of solid tumors. The tumor endothelium exists in a state of chronic activation and proliferation, fueled by the tumor milieu where angiogenic mediators are aberrantly over-expressed. Uncontrolled tumor growth, immune evasion, and therapeutic resistance are all driven by the dysregulated and constitutive angiogenesis occurring in the vasculature. Accordingly, great efforts have been dedicated toward identifying molecular signatures of this pathological angiogenesis in order to devise selective tumor endothelium targeting therapies while minimizing potential autoimmunity against physiologically normal endothelium. Vaccination with angiogenic antigens to generate cellular and/or humoral immunity against the tumor endothelium has proven to be a promising strategy for inhibiting or normalizing tumor angiogenesis and reducing cancer growth. Here we review tumor endothelium vaccines developed to date including active immunization strategies using specific tumor endothelium-associated antigens and whole endothelial cell-based vaccines designed to elicit immune responses against diverse target antigens. Among the novel therapeutic options, we describe a placenta-derived endothelial cell vaccine, ValloVax™, a polyvalent vaccine that is antigenically similar to proliferating tumor endothelium and is supported by pre-clinical studies to be safe and efficacious against several tumor types.